Prevalence of Trachoma in Senegal: Results of Baseline Surveys in 17 Districts. (28th December 2018) - Sarr, Boubacar; Sissoko, Mactar; Fall, Mawo; Nizigama, Lionel; Cohn, Daniel; Willis, Rebecca; Fuller, Brian; O'Neil, Maggie; Solomon, Anthony W; ,
ABSTRACT: Purpose : Senegal is endemic for trachoma, an infectious and potentially blinding eye disease. To complete the country's district-level baseline map of trachoma, we conducted population-based surveys in 17 health districts that were suspected-endemic but had yet to be surveyed. Methods : We randomly selected 30 clusters (villages) per district and 30 households per village, and estimated the district-level prevalences of trachomatous inflammation—follicular (TF) in children aged 1–9 years, and trichiasis in persons aged ≥15 years. Data on household-level water, sanitation, and hygiene variables were also collected. Global Trachoma Mapping Project methods were followed in training, fieldwork, and data handling. Results : 25, 704 children aged 1–9 years and 30, 345 adults aged 15 years and above were examined. In children aged 1–9 years, the prevalence of TF was <5% in all 17 districts, with the exception of Saint-Louis (5.1%, 95% CI 3.2–7.5). Trichiasis prevalence in participants aged 15 years and above ranged by district from 0%–1.1% (95% CI 0.7–1.5), with 9 districts having trichiasis prevalences above the elimination threshold of 0.2%. Trichiasis was seen to be significantly less frequent in males than in females (0.17% [95% CI 0.12–0.24] versus 0.49% [95% CI 0.38–0.61], p  < 0.001). The prevalence of trichiasis rose steeply with age; 62% of cases were observed in people aged 55 years or above. Conclusions : Active trachoma is not a public health problem in 16 of the 17 surveyed districts, and implementation of the full Surgery (S) – Antibiotics (A) – Facial cleanliness (F) – Environmental improvement (E) strategy is not a programmatic priority. Increased provision of trichiasis surgery is warranted in nine districts.